Regards sur les systèmes de paiements pour services écosystémiques en milieu agricole au Québec - Sophie Lavallée; Jérôme Dupras (Développement Durable et Territoires)
Despite the growing interest they arouse, market instruments, such as payments for ecosystem services (PES), are still far from being the dominant political strategies in the conservation of biodiversity and protection of the environment, in Quebec as elsewhere. Even though the PES have received greater consideration in recent years, the field of legal studies regarding this question has hardly progressed. Within this context, the aim of this paper is twofold. Firstly, it aims to provide an overview of the different political systems incorporating the concept of ES in Quebec and to identify the role it occupies within these arrangements. Secondly, it also aims to consider more specifically how PES Programs implemented in the agricultural sector of Quebec can help improve existing political arrangements in this sector.